2012
DOI: 10.1002/masy.201100191
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Experimental Design for Obtaining Nanocellulose from Curaua Fiber

Abstract: This study focuses on the methodology to obtain nanocellulose from vegetal fibers. An experimental planning was carried out for the treatment of curaua fibers and parameters were estimated, having the concentration of H 2 SO 4 , hydrolysis time, reaction temperature and time of applied sonication as independent variables for further statistical analysis. According to the estimated parameters, the statistically significant effects were determined for the process of obtaining nanocellulose. With the results obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Then the fibers were repeatedly washed with deionized water until the pH of washings reached neutrality. The material was dried under vacuum until constant weight [20].…”
Section: Chemical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the fibers were repeatedly washed with deionized water until the pH of washings reached neutrality. The material was dried under vacuum until constant weight [20].…”
Section: Chemical Treatmentmentioning
confidence: 99%
“…However, this process is quite expensive and harmful for the environment. In a previous study [20], we evaluated the treatment of curauá fiber with sulfuric acid at different conditions (concentration, time, and temperature) and observed that treatment with low concentration of the acid may weaken the fiber surface, allowing fibrillation during processing in an extruder under conditions of shear at elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The fibers were extensively washed with water and then they were slightly hydrolyzed with a solution of sulfuric acid (10 wt%) at 40 °C for 240 min under continuous stirring. This process is described in detail elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…This improvement in compatibility generates better interfacial interaction, which enhances the composite's mechanical performance . Lunz et al conducted an experiment to assess the best conditions to remove the amorphous fractions in curauá fibers, finding an increase in the fiber crystallinity degree. The authors also treated curauá fibers with sulfuric acid under different conditions (concentration, time and temperature) and observed that treatment with low acid concentration can weaken the fiber surface, allowing fibrillation during processing in an extruder under conditions of shear at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we investigated jute fibers, chemically treated in the same conditions as a previous work with curauá, and compared both jute and curauá fibers with other sources of cellulose (commercial Arbocel ® and amorphized cellulose using ball milling), for potential use as reinforcing filler in polycaprolactone matrices, by evaluating the performance of the resulting composites. The innovation of this work is the assessment of using chemically treated natural fibers to promote an increase in PCL mechanical properties without affecting its thermal resistance, broadening the range of uses in other packaging and medical areas.…”
Section: Introductionmentioning
confidence: 99%